2023
DOI: 10.3390/antibiotics12020388
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Activity Testing of a Modular Fusion Peptide against Enterococcus faecalis

Abstract: The emergence of antibiotic resistance in enterococci is a great concern encountered worldwide. Almost all enterococci exhibit significant levels of resistance to penicillin, ampicillin, semi-synthetic penicillin and most cephalosporins, primarily due to the expression of low-affinity penicillin-binding proteins. The development of new and novel antibacterial agents against enterococci is a significant need of the hour. In this research, we have constructed a modular peptide against Enterococcus faecalis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Almost 100% of the protein was bound to the cell pellet and no protein was seen in the unbound supernatant fraction (Figure 3A: Lane 2 and Lane 4). In corroboration with a previously observed result described by Manoharadas et al [34], BP404 was able to bind to the E. faecalis clinical strain at a much lower rate, with only approximately 20% of the protein bound to the cell pellet (Figure 3B: Lane 1). Similarly, BP404 was also able to bind to S. aureus Rumba, but at a very low intensity (approximately 15-20%, Figure 3B: Lane 3).…”
Section: P16-17/100 and Bp404 Displays Cell-wall Binding Towards S Au...supporting
confidence: 92%
See 4 more Smart Citations
“…Almost 100% of the protein was bound to the cell pellet and no protein was seen in the unbound supernatant fraction (Figure 3A: Lane 2 and Lane 4). In corroboration with a previously observed result described by Manoharadas et al [34], BP404 was able to bind to the E. faecalis clinical strain at a much lower rate, with only approximately 20% of the protein bound to the cell pellet (Figure 3B: Lane 1). Similarly, BP404 was also able to bind to S. aureus Rumba, but at a very low intensity (approximately 15-20%, Figure 3B: Lane 3).…”
Section: P16-17/100 and Bp404 Displays Cell-wall Binding Towards S Au...supporting
confidence: 92%
“…In addition, we also wanted to test if protein P16-17/100 was able to bind to S. aureus Rumba and E. faecalis clinical isolate. It was earlier shown that BP404 was able to bind to E. faecalis clinical isolate, but not very efficiently [34]. As shown in Figure 3A, protein P16-17/100 could efficiently bind to both E. faecalis clinical isolate (Figure 3A: Lane 1) and S. aureus Rumba (Figure 3A: Lane 3).…”
Section: P16-17/100 and Bp404 Displays Cell-wall Binding Towards S Au...mentioning
confidence: 82%
See 3 more Smart Citations